Identification of lipid metabolism-associated genes as prognostic biomarkers based on the immune microenvironment in hepatocellular carcinoma - Gu, Xiangqian; Jiang, Chenshan; Zhao, Jianguo; Qiao, Qian; Wu, Mingyu; Cai, Bing (Frontiers in Cell and Developmental Biology, 2022)
Lipid metabolism is associated with progression of various cancers. Nevertheless, the underlying mechanisms of lipid metabolism associated genes (LMAGs) effect on tumor immune microenvironment has not been well uncovered. This study aimed at discovering the effect of lipid metabolism on tumorigenesis and development of hepatocellular carcinoma (HCC). Expression files and clinical data of HCC patients were obtained from TCGA and ICGC databases. Consensus clustering was performed to build new subgroups. Using Cox Regression and Lasso Regression analysis, a prognostic risk model was constructed based on LMAGs. Tumor mutation burden (TMB), immune cell infiltration levels and immune response checkpoints of identified risk groups were determined and compared. Two clusters based on LMAG expression were identified, showing a significant difference in tumor stage and immune cell infiltration. Then, a prognostic risk model based on four LMAGs was constructed and proved to have great value in predicting prognosis. Patients in high-risk groups showed a worse survival than those in low-risk groups, which might be associated with the TP53 mutation status, TMB score, immunocyte infiltration degrees and immune checkpoint levels. Likewise, expression level of every LMAG included in the model had the same effect on overall survival and immune cell infiltration levels. More importantly, the prognostic value of prognostic signature was verified in independent ICGC cohort. Expression levels of LMAGs were closely related with tumor microenvironment of HCC and could be promising as biological indicators for prognosis and immune therapy plan in HCC patients.